2021
DOI: 10.1093/conphys/coaa115
|View full text |Cite
|
Sign up to set email alerts
|

Using claws to compare reproduction, stress and diet of female bearded and ringed seals in the Bering and Chukchi seas, Alaska, between 1953–1968 and 1998–2014

Abstract: Rapid climate warming is decreasing sea ice thickness, extent and duration. Marine mammals such as bearded (Erignathus barbatus) and ringed (Pusa hispida) seals, which use sea ice for pupping, molting and resting, may be negatively affected. Claws from bearded and ringed seals store up to 14 and 12 years of sequential analyte data, respectively. These data can be used to compare reproduction, stress and diet across decades. In this study, we compare progesterone, cortisol and carbon and nitrogen stable isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…The results of our study suggested there are potential management benefits from using historical samples to evaluate population-level changes in reproductive and stress-related steroid hormones due to environmental stressors or changes in reproductive activity over periods of time. Further, additional physiological parameters such as dietary stable isotopes, trace minerals, or contaminants can be determined in both hair and claw tissues and are incorporated during growth and are therefore temporally linked to hormone concentrations in the same tissue allowing for exploring potential stressors (Bechshøft et al 2012b(Bechshøft et al , 2015Crain et al 2021; M. J. Keogh, ADF&G, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of our study suggested there are potential management benefits from using historical samples to evaluate population-level changes in reproductive and stress-related steroid hormones due to environmental stressors or changes in reproductive activity over periods of time. Further, additional physiological parameters such as dietary stable isotopes, trace minerals, or contaminants can be determined in both hair and claw tissues and are incorporated during growth and are therefore temporally linked to hormone concentrations in the same tissue allowing for exploring potential stressors (Bechshøft et al 2012b(Bechshøft et al , 2015Crain et al 2021; M. J. Keogh, ADF&G, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have measured stress‐related or reproductive hormones in claws of other species (Baxter‐Gilbert et al 2014, Karpovich et al 2020, M. J. Keogh, ADF&G, unpublished data), our study is the first attempt to measure hormones in wolf claws. Additionally, we measured hormones in archived tissue samples collected from 4–25 years ago, demonstrating the potential to assess changes in stress and reproductive hormone concentrations in populations over decades (Bechshøft et al 2012 a , Hunt et al 2016, Crain et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of hormone in hair is further complicated by potential seasonal variation in pelage growth rates and hair lengths ( Maurel et al, 1986 ), whereas claw growth remains relatively consistent in most species examined ( Ethier et al, 2010 ). Although used in turtles ( Baxter-Gilbert et al, 2014 ); chameleons ( Matas et al, 2016 ); cattle ( Comin et al, 2014 ); seals ( Karpovich et al, 2020 ; Crain et al, 2021 ); cats ( Contreras et al, 2021 ); and dogs ( Mack and Fokidis, 2017 ; Jasmine et al, 2018 ), little research has investigated how claw GC concentrations differ within and among free-living individuals, nor explored the sources of this variation.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian claws include soft internal structures covered by a rigid horn above [23]. The external keratin horn might include the periodically banded structures; this fact proves the presence of annual differences in physiological condition of the animal [24]. The reptile claw comprises bone of distal phalanx and epidermal sheath, with keratinized corneus of the unguis an less keratinized subunguis epidermis [25,26].…”
Section: Introductionmentioning
confidence: 99%